Qualidade fisiológica de sementes de cenoura e abóbora classificadas por tamanho - Santos, Valdecir José dos (2009)
Carrot (Daucus carota L.) and pumpkin (Cucurbita moschata) production is very important as food because they have important nutritional and pharmacological properties. High physiological quality of seeds of these species are subjected to high heterogeneity at maturation. Classification of seeds by size can be an alternative in order to improve physiological quality of seed lots. The aim of this study was to discriminate physiological quality of seed lots using mean comparison by orthogonal contrasts and identify tests that estimate the performance of seeds classified by size. Thus, an experiment was conducted using three lots of different seed sizes (medium, large and extra large) of carrot, cultivars Brasília and Alvorada, and of pumpkin, cultivar Menina Brasileira. Length of seedlings is a variable used to characterize physiological seed potential. However, this test can present experimental errors due to lossing parts of seedlings or inaccuracy in measurements. In order to correlate size of seeds and length of seedlings measured by a millimeter ruler with the method of digital images, another experiment was carried out. Due to high correlation found between the variables valued by the imaging method and measured with millimeter ruler, the method of digital images can be indicated as an alternative to measure seed size and seedlings length. Lots of medium seeds compared with lots of greater (large an extra large) seeds showed differences in physiological quality, justifying classification of seeds by size. In carrot cultivars Brasilia and Alvorada size of seeds did not influence germination, shoot lenght and total seedling length. However significant differences were found in dry weight of seedlings, seed weight and length of root, showing that the last variable, in addition to dry weight, was the most sensitive to separate lots by vigor. Pumpkin showed germination, first count of germination and cold test, respectively, 14.75%, 22.35% and 19.20% higher for extra large seeds in relation to large seed. Means comparison by orthogonal contrasts is an adequate analysis to discriminate physiological quality of carrot and pumpkin seed lots.